Infection avoidance behavior: Viral exposure reduces the motivation to forage in female Drosophila melanogaster. Issue 1 (2nd January 2017) - Vale, Pedro F.; Jardine, Michael D.
ABSTRACT: Infection avoidance behaviors are the first line of defense against pathogenic encounters. Behavioral plasticity in response to internal or external cues of infection can therefore generate potentially significant heterogeneity in infection. We tested whether Drosophila melanogaster exhibits infection avoidance behavior, and whether this behavior is modified by prior exposure to Drosophila C Virus (DCV) and by the risk of DCV encounter. We examined 2 measures of infection avoidance: (1) the motivation to seek out food sources in the presence of an infection risk and (2) the preference to land on a clean food source over a potentially infectious source. While we found no evidence for preference of clean food sources over potentially infectious ones, previously exposed female flies showed lower motivation to pick a food source when presented with a risk of encountering DCV. We discuss the relevance of behavioral plasticity during foraging for host fitness and pathogen spread.